Ambivalenza della vita umana. Tra la materialità corporale e l'ontologia del "vulnerabile" nel pensiero di Judith Butler - Rosenzweig, Esteban (AG About Gender. Rivista Internazionale di studi di genere.)
The present work is aimed at establishing a conceptual correspondence between the notions of body and corporal materialization proposed by Judith Butler, until they converge on the theoretical core of that concept the philosopher designates as "common human vulnerability". In what way do we think of human life? What value do we have to give life, without turning and ontologically transforming it into something essential? These questions will trigger the following reflexions.